MYKHAILO YATSKIV FOREVER - Babii, Vasyl (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The purpose of the article is analytical judgments about the work of one of the bright representatives of Western Ukrainian modernism, Mykhailo Yatskiv (1873-1961). The object of research was the prose works of the writer, and the subject of study was the peculiarities of Halychyna novelist’s artistic thinking. The author of the article, dedicating it to the 150th anniversary of the birth of the famous artist of words, reveals through the prism of biographical information the works (stories, novels) of Mykhailo Yatskiv, his style of writing, connected with psychologization, whimsy and modernity of his author’s ideological and aesthetic consciousness. At the same time, analyzing the literary heritage of the novelist, he uses the following research methods: biographical, hermeneutic, philological, and comparative-typological. Such a methodological synthesis contributes to the disclosure of the epic thinking of the writer, in particular its modernist component. The scientific novelty of this study lies in the fact that it collects and organizes little-known (or unknown) and modern scientific works about the herritage of Mykhailo Yatskiv, and an attempt to analyze the writer’s stories and novels using new methodological approaches is used. The practical significance of the publication is realized already in its title: the work of Mykhailo Yatskiv can be used at any time in educational institutions (at Ukrainian literature classes, in special courses and seminars in higher education), in works about the heritage of Mykhailo Yatskiv.